Stories from English History - Skae, Hilda T. (Salt Lake City, UT : Project Gutenberg, 2008)
"Stories from English History" by Hilda T. Skae is a collection of historical tales written in the early 20th century. This work aims to bring history to life for younger readers, allowing them to engage with real events and people from England's past. The book covers a variety of significant figures and moments throughout English history, beginning with the ancient Briton Caradoc and his battles against the Romans. The opening of this historical account introduces readers to the tumultuous times when ancient Britain was inhabited by fierce Britons resisting Roman conquest. Caradoc, the noble chieftain, emerges as a key figure in this struggle for freedom, refusing to submit to Roman rule despite facing overwhelming odds. The narrative sets the stage for his guerrilla tactics against the Romans, showcasing the bravery of the Britons as they fight to protect their homeland. Additionally, themes of loyalty and betrayal are foreshadowed as Caradoc's resilience against invaders leads to significant consequences for himself and his family, highlighting the complexities of leadership during wartime. (This is an automatically generated summary.)
Release date is 2008-03-01
E-text prepared by Al Haines
Keywords: Great Britain -- History -- Juvenile literature